STUDI TENTANG FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN STATUS KESEHATAN GIGI DAN MULUT SISWA SMK YAPENDA WIRADESA KABUPATEN PEKALONGAN - Imam Purnomo; Sri Lestari (LPPM Universitas Pekalongan, 2013)
Healthy is the result of 3 (three) condition they are, physique, mental and social that interact each other. Thus, status of dental health and mouth are also the result of interaction between physique, mental and social. Factors that affect status of dental health and mouth are knowledge, kind of consumed snacks, way to brush teeth, way to check teeth, and smoking habit. The purpose of the study is to find out factors related to dental health students’ mouth of SMK Yapenda Wiradesa, Pekalongan regency. In conducting the research, the writer used survey of analytic by using Cross Sectional approach. The populations of the study are all students of SMK Yapenda Wiradesa. The sample are 208 populations that are taken by using simple random sampling. The instrument in this study is questionnaire. Data analysis was done univariately and bivariately using Chi Square test with α = 0,5. The result of the study shows that there is a relationship between knowledge (p = 0,032), kind of consumed snakcs (p = 0,000), way to brush teeth (p = 0,016) and status of dental and mouth heatlth students’ of SMK Yapenda Wiradesa, Pekalongan regency. It is suggested to pay attention kind of consumed snacks such as chocolate and candy reduced in amount, to brush teeth twice a day, to check to dentist, to visit school, and to hold counseling and checkup.Keywords : Knowledge, kind of snacks, way to brush teeth, Status of dental health and mouth.